Just a Larger Family : Letters of Marie Williamson from the Canadian Home Front,1940-1944 - Williamson, Marie, 1898-1969 (Book collections on Project MUSE., 2011)
Marie wrote over 150 letters to Margaret Sharp between August 1940 and May 1944, imagining that she could make Margaret feel she was still with her children. She shepherded the boys through education decisions and illnesses, eased their adaptation to a strange new life, and rejoiced when they embraced unfamiliar winter sports. The letters brim with detail about food shortages and rationing, family holidays, the family's efforts to cope with the financial implications of two extra mouths to feed, their involvement in their church, and the games and activities that kept them occupied. Marie's letters reflect the lives and concerns of a particular family in Toronto, but they also reveal a portrait of what was then Canada's second-largest city during wartime. --pub. desc.